2018
DOI: 10.11591/ijece.v8i6.pp5260-5267
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Bandwidth of Band Pass Filter Using a Defected Microstrip Structure for Wideband Applications

Abstract: <p>In this paper, the bandwidth enhancement of bandpass filter (BPF) is proposed by utilizing defected microstrip structure (DMS). The initial micro strip BPF which is designed to have the bandwidth 1GHz with the center frequency of 3.5GHz is deployed on FR4 Epoxy dielectric substrate with overall size and thickness of 14mm x 24mm and 1.6mm, respectively. The proposed filter consists of two parallel coupled lines centred by ring-shaped, to enhance the bandwidth response, an attempt is carried out by appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In order to reduce the dimensions of the designed resonator, the DMS technique [12][13][14] is employed to minimize the circuit size by etching slots in the microstrip line which disturbs the current distribution. As shown in figure 6, a slot DMS is integrated into the microstrip line of…”
Section: Jinst 16 P11013mentioning
confidence: 99%
“…In order to reduce the dimensions of the designed resonator, the DMS technique [12][13][14] is employed to minimize the circuit size by etching slots in the microstrip line which disturbs the current distribution. As shown in figure 6, a slot DMS is integrated into the microstrip line of…”
Section: Jinst 16 P11013mentioning
confidence: 99%
“…We observed that the proposed concept has advantages in terms of availability of synthesis, exhibit transmission zero and narrow bandwidth of less than 6% compared to others. [20] Yes No 10 % [21] Yes No 50 % [22] No Yes 5.69 % [23] No Yes 80 % [24] No Yes 98.73 % [25] No Yes 52.17% [26] No…”
Section: Nd and 3 Rd Order Filter Realizationmentioning
confidence: 99%
“…However, the reported work in [3] has poor selectivity from passband to stopband region. Other methods such as defected ground structure (DGS) and slotted structure to design of filters have been proposed, but the main problem is complexity of fabrication process [4][5][6][7]. In [4], the bandwidth of filter has been increased by a DGS structure.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods such as defected ground structure (DGS) and slotted structure to design of filters have been proposed, but the main problem is complexity of fabrication process [4][5][6][7]. In [4], the bandwidth of filter has been increased by a DGS structure. The filter based on DGS in [5] has wide stopband.…”
Section: Introductionmentioning
confidence: 99%